The clustering and halo occupation distribution of Lyman-break galaxies at z ∼ 4. Issue 1 (7th June 2016) - Park, Jaehong; Kim, Han-Seek; Wyithe, J. Stuart B.; Lacey, C. G.; Baugh, C. M.; Barone-Nugent, R. L.; Trenti, M.; Bouwens, R. J.
Abstract: We investigate the clustering of Lyman-break galaxies (LBGs) at z  ∼ 4. Using the hierarchical galaxy formation model GALFORM, we predict, for the first time using a semi-analytical model with feedback from active galactic nuclei (AGN), the angular correlation function (ACF) of LBGs and find agreement within 3σ with new measurements of the ACF from surveys including the Hubble eXtreme Deep Field (XDF) and Cosmic Assembly Near-infrared Deep Extragalactic Legacy Survey (CANDELS) field. Our simulations confirm the conclusion reached using independent models that although the predicted ACFs reproduce the trend of increased clustering with luminosity, the dependence is less strong than observed. We find that for the detection limits of the XDF field, central LBGs at z  ∼ 4 predominantly reside in haloes of mass ∼10 11 –10 12   h −1  M⊙ and that satellites reside in larger haloes of mass ∼10 12 –10 13   h −1  M⊙ . The model predicts fewer bright satellite LBGs at z  ∼ 4 than is inferred from measurements of the ACF at small scales. By analysing the halo occupation distribution (HOD) predicted by the model, we find evidence that AGN feedback affects the HOD of central LBGs in massive haloes. This is a new high-redshift test of this important feedback mechanism. We investigate the effect of photometric errors in the observations on the ACF predictions. We find that the observational uncertainty in the galaxy luminosity reduces the clustering amplitude and that this effect increases towards faint galaxies, particularly on small scales. To compare properties of model with observed LBGs, this uncertainty must be considered.